Impact of Asthma on the Development of Coronary Vasospastic Angina: A Population-Based Cohort Study. Issue 42 (October 2015) - Hung, Ming-Jui; Mao, Chun-Tai; Hung, Ming-Yow; Chen, Tien-Hsing
Abstract : Abstract: Although asthma increases the risk of cardiovascular disease, little is known about the relation of asthma and its severity to coronary vasospastic angina (CVsA). We hypothesized that asthma contributed to the development of CVsA. Patients in this population-based cohort study were retrospectively collected from the Taiwan National Health Insurance database. Using propensity score matching, subjects were stratified at a 1 : 4 ratio into a study group comprising 3087 patients with a diagnosis of CVsA, and a control group consisting of 12, 348 patients who underwent coronary intervention for obstructive coronary artery disease (CAD) during the period 2000 to 2011. Asthma significantly increased the risk of new-onset CVsA independent of other comorbidities [adjusted odds ratio (OR) = 1.85, 95% confidence interval (95% CI) = 1.47–2.32, P < 0.001]. In addition, the risk of new-onset CVsA was significantly higher in previous users of oral or inhaled corticosteroids (oral corticosteroids: OR = 1.22, 95% CI = 1.01–1.49, P = 0.04; inhaled corticosteroids: OR = 1.89, 95% CI = 1.28–2.79, P = 0.001). In addition, the prevalence of asthma was highest among patients with CVsA alone, followed by patients with CAD and CVsA and patients who underwent coronary intervention for CAD alone ( P trend < 0.001). Our study suggests that asthma is independently associated with CVsA and prior steroid use increases the risk of CVsA development.